Characteristics of lung metastasis in testicular cancer: A large-scale population analysis based on propensity score matching - Guo, Aiyuan; Gu, Jie; Yang, Jiayi (Frontiers in Surgery, 2022)
Background: To systematically evaluate predictive factors for lung metastases (LM) in patients with testicular cancer (TC) and to investigate cancer-specific survival (CSS) and overall survival (OS) of LM in TC patients based on large, population-cohort. Methods: A total of 10414 Patients diagnosed with TC during 2010-2015 were adopted from the Surveillance, Epidemiology and End Results (SEER). After propensity score matching (PSM), 493 patients with LM were included for subsequent analysis. Univariate and multivariate logistic-regression were employed to identify risk factors, and a nomogram was developed and the receiver operating curve (ROC) was utilized to confirm the validation of the nomogram. Prognostic factors for OS and CSS among TC patients with LM were estimated via Cox proportional hazards models. Results: Postmatching indicated that 11 parameters were successfully balanced between both groups (P > 0.05). After PSM, TC patients with LM presented undesirable prognosis in both CSS and OS than those without LM (P < 0.001). Logistic-regression model showed tumor size, T stage, N stage, liver, brain and bone metastases and histology positively associating with LM (P < 0.05). A nomogram was developed to predict diagnostic possibilities based on the independent risk variables, and the ROC curve verify the predictive capacity of the logistic-regression model (AUC=0.910). Conclusion: The nomogram can be predictive criteria for TC patients with LM. Brain metastases, liver metastases and larger tumor size were prognostic factors for CCS and OS among TC patients with LM.